Long-term results of hip arthroplasty and determination of unfavorable risk factors for early development of osteonecrosis in patients with systemic lupus erythematosus - V. V. Mukhanov; S. A. Makarov; M. A. Makarov; T. V. Popkova (Научно-практическая ревматология)
Aim of the study – to determine the risk factors for the early development of osteonecrosis and to analyze the results of surgical treatment of patients with systemic lupus erythematosus in the long term after total hip arthroplasty.Materials and methods. The study group included 42 patients with systemic lupus erythematosus (SLE) complicated by osteonecrosis (ON) of the femoral head, who underwent 59 total hip arthroplasty (THA) operations. Before surgery and 6–21 years after THA, in order to assess the long-term results of surgical treatment of patients, the following was assessed: activity of the underlying disease – according to the SLEDAI-2K (Systemic Lupus Erythematosus Disease Activity Index 2000); the severity of irreversible changes in internal organs – according to the SLICC/ACR index of damage (Systemic Lupus International Collaborating Clinics/American College of Rheumatology); the clinical and functional state of the hip joint – according to the HHS (Harris Hip Score); the intensity of pain syndrome – according to the visual analogue scale (VAS); quality of life (QOL) – using the SF-36 questionnaire. The concentration of antibodies to cardiolipin (aCL) of IgM and IgG isotypes was determined by enzyme-linked immunosorbent assay (normal range – 0.0–10.0 GPL for IgM, 0–7 MPL for IgG).Results. After 6–21 years of follow-up after THA, there was a statistically significant decrease in pain intensity according to VAS, improvement according to the HHS from 40.0±14.9 to 83.3±17.4 points, SLE activity according to the SLEDAI-2K from 0 to 20 points (median – 4 [4; 8] points) before surgery and from 0 to 41 points (median – 0 [0; 4] points) after a long period of observation. There was a pronounced statistically significant positive dynamics for all QOL indicators studied (p≤0.005 in all cases). The most significant changes were found on the scales RE (Role-Emotional), RP (Role-Physical Functioning) and BP (Bodily Pain). The early development of ON was associated with the degree of activity of the underlying disease, the cumulative dose of glucocorticoids, kidney damage and arthritis in the first year from the onset of SLE, as well as hematological disorders and the presence of aCL in the blood serum 3 years before the onset of ON. The total number of complications was 10.2%.Conclusion. Total hip arthroplasty in patients with systemic lupus erythematosus can achieve a statistically significant reduction in pain intensity, increase functional activity and improve their quality of life.